Effects of Vitamin D Supplementation on C-peptide and 25-hydroxyvitamin D Concentrations at 3 and 6 Months - Chandler, Paulette D. (Sci Rep, 2015)
The link between African-Americans’ disproportionate rates of diabetes, obesity and vitamin D deficiency may be marked by C-peptide as an indicator of insulin secretion. We hypothesize that vitamin D supplementation will increase C-peptide, a marker of insulin secretion. During 3 winters from 2007-2010, 328 healthy African-Americans (median age, 51 years) living in Boston, MA were randomized into a 4-arm, double-blind trial for 3 months of placebo, 1000, 2000, or 4000 IU of vitamin D3. The differences in non-fasting C-peptide between baseline and 3 months were −0.44 ng/mL for those receiving placebo, −0.10 ng/mL for those receiving 1000 IU/d, 0 ng/mL for those receiving 2000 IU/d, 1.24 ng/mL for those receiving 4000 IU/d (C-peptide increased 0.42 ng/mL for each additional 1000 IU/d of vitamin D3, p < 0.001). Vitamin D supplementation increased C-peptide in overweight African-Americans and may be compatible with other recommendations for diabetes prevention and management including weight loss and increased physical activity.